Peningkatan Hasil Belajar Peserta Didik Melalui Model Problem Based Learning Pada Mata Pelajaran Fiqih Bab Zakat di Kelas VIII MTs Darul Hikam Semester 1 Tahun Pelajaran 2020/2021 - Abdur Rouf (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2020)
One of the problems facing our education world is the problem of weak learning processes. In the learning process, children are less encouraged to develop thinking skills. The learning process in the classroom is directed to the child's ability to memorize information; Children's brains are forced to remember and hoard various information, required to understand the information they remember to connect it to everyday life. The formulation of the problem in this study is how the application of problem-based learning models can improve student learning outcomes in the material zakat class VIII MTs Darul Hikam Tracal Karanggeneng Lamongan. Research methods using action research or action research is a research model that is at the same time practising and theorizing, or combining theory while implementing in practice. The results of the study mentioned that the application of problem-based learning models on zakat material can improve the learning outcomes of students of class VIII MTs. Darul Hikam Tracal Karanggeneng Lamongan. The increase is seen from the average posttest value of cycle I which is 74.94 with a completion value of 82.35%. While in cycle II, it is 43.53 to 81.41 and in cycle III from 52.47 to 89.18. Thus the application of the problem-based learning model is considered successful in improving student learning outcomes in zakat provision material because it has achieved the indicators of success that have been established.